If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (I)(5i)(4 + -3i) = 0 Remove parenthesis around (5i) I * 5i(4 + -3i) = 0 Reorder the terms for easier multiplication: 5I * i(4 + -3i) = 0 Multiply I * i 5iI(4 + -3i) = 0 (4 * 5iI + -3i * 5iI) = 0 (20iI + -15i2I) = 0 Solving 20iI + -15i2I = 0 Solving for variable 'i'. Factor out the Greatest Common Factor (GCF), '5iI'. 5iI(4 + -3i) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'iI' equal to zero and attempt to solve: Simplifying iI = 0 Solving iI = 0 Move all terms containing i to the left, all other terms to the right. Simplifying iI = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(4 + -3i)' equal to zero and attempt to solve: Simplifying 4 + -3i = 0 Solving 4 + -3i = 0 Move all terms containing i to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3i = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3i = 0 + -4 -3i = 0 + -4 Combine like terms: 0 + -4 = -4 -3i = -4 Divide each side by '-3'. i = 1.333333333 Simplifying i = 1.333333333Solution
i = {1.333333333}
| (83-x)+(5x+11)=10 | | (3x+2)(2x-1)=-(3x+1) | | 7y+9=6y-2 | | 645-07-04-00-00_files/i0090000.jpg | | (83-x)=180 | | 3=x/3.3 | | (0,29x)/(0,4-0,4x^2,39) | | x/6=3/4 | | x^8+254x^4+1=0 | | (5x+11)=180 | | (M-9)+6=4(m-2)-2(m-6) | | 2x+13=-5x-7x | | 18a/6 | | (7+5i)+(5i)= | | (x-2x/100)*60/100*70/100=7203 | | (5x+11)=360 | | (-8i)-(3i)= | | 4d=1/3 | | x+(3x+15)=135 | | 256x^2=-176 | | Y+5-6y=17-2y | | 1.2c=0.6 | | (3i)-(I)= | | 3d+5d+9d-8= | | f(x)=6x^3+11x^2-10x | | (8j-9)=14 | | 6=3/5w | | 4(d+3)= | | 2w-3=2w | | a+5a+4b= | | 1.6x=2.5y+2 | | 7v/6=42 |